Response surface modeling for biodiesel optimization in one-stage and two-stage transterification at 32degreeC and 65degreeC - Ticao, Rhe Jay Cambarijan (2005)
Cocodiesel is a type of biodiesel which is derived from the coconut oil. The most commonly used method in biodiesel production is transesterification, either one-stage or two-stage. In an initial study on the production of biodiesel, two-stage transesterification resulted in 98.74% CME conversion. However, it is still needed to standardize the input variables in order to optimize biodiesel production using one-stage and two-stage transesterification at 320C and 65oC. Each process of transesterification at different temperature was subjected to response surface modeling. Results showed that the optimum combination of catalyst and alcohol for one-stage transesterification at room temperature are 0.7209 g and 31.1309 g, respectively, with 81.84% CME conversion. Optimum combination of catalyst and alcohol of one-stage transesterification at 65oC are 0.7329 g and 33.4587 g, respectively, with 83.18% CME conversion. For two-stage transesterification at room temperature, the optimum combination of catalyst and alcohol are 0.6408 g and 28.8731 g, respectively, with a 94.57% CME conversion. On the other hand, the optimum combination of catalyst and alcohol for two-stage transesterification at 65oC are 0.8102 g and 28.6267 g, respectively, with a 97.60% CME conversion. Thus, two-stage transesterification emerge to be more favorable. It would be advantageous to apply two-stage transesterification particularly at 65oC as it gave maximum CME and consequently greater revenue